Desain Pembelajaran Berbasis Literasi-Orientasi-Kolaborasi-Refleksi (LOK-R) untuk Meningkatkan Kemampuan Mahasiswa Mereview Artikel Ilmiah - M. Zainudin; Ahmad Kholiqul Amin; Ima Isnaini Tufiqur Rohmah (Journal on Education, 2024)
Literature review is one of the foundations for conducting research. This research aims to produce a learning model design based on Literacy, Orientation, Collaboration and Reflection (LOK-R). This development research adapts the Borg and Gall model, namely 1) needs analysis, 2) product design, 3) product development, 4) product implementation and evaluation. Thirty-one students from the Mathematics Education study program at IKIP PGRI Bojonegro were selected for this research through cluster random sampling. The instruments used in this research include (1) learning design validation guidelines, (2) practical learning implementation guidelines and (3) skill tests for reviewing articles in accredited national journals. Improvement in article reviewing skills is measured using an article review skills test instrument in accredited national journals. This research used two tests, namely a pre-test carried out before treatment and a post-test carried out after treatment. Data analysis in this research used SPSS version 22 statistical software. The results of this research produced a valid, practical and effective LOK-R based learning model design for improving the ability to review articles. The LOK-R based learning model consists of components (1) learning syntax consisting of steps, namely (a) literacy, (b) orientation, (c) collaboration (d) reflection. Reflection in learning in the form of conveying the results that have been learned and constructive comments from colleagues and assessing one's own results